Dynamics of Capability Upgrading in Indonesian Herbal Medicine Firms - Erman Aminullah (National Research and Innovation Agency, Indonesia, 2022)
This article examined the dnamics of capability upgrading in Indonesian herbal medicine firms for empirical and future trends analysis. The dynamics of capability upgrading was analysed by using system dynamics modelling. New knowledge was revealed from system dynamics analysis of capability upgrading in Indonesian herbal medicine firms, the core ideas are: capability upgrading in Indonesian herbal medicine firms can be realized by two routes: i. the linier moving up of technological capability ladders from traditional herbal to standardized herbal and phytopharmaceutical medicine, and, ii. the non-linier dynamic of technological capability upgrading by directly producing standardized herbal by using R&D and then move-up to create phytopharmaceutical medicine. The enabler factors of company’s success in capability upgrading were innovation collaboration and management coordination led by top management. The process of capability upgrading can be accelareted by incporporating: advanced knowledge base (such as biotechnology), the entrepreneurial activities of leading firms, and institutional/regulatory support from the government.. Keywords: capability upgrading, herbal medicine, system dynamics, future trends, enabler factors.